Greenfield investments as a source of sustainable green finance? On the relationships between greenfield investments, environmental performance, and asian economic growth - Rabindra Nepal; Farhad Taghizadeh-Hesary; Hameed Musibau (Asian Development Bank Institute (ADBI), 2020)
Can economic growth continue without degrading the quality of the environment? This question has led to a lot of inconclusive findings among researchers. This study examines the impact of greenfield investment, human capital, economic activities, and the role of institutions on the environment among Asian countries for the period 2000-2018. The Environmental Performance Index (EPI) developed by Yale University is used as a proxy for gauging environmental performance. The econometric technique is based on panel data econometrics that accounts for cross-sectional dependence, possible endogeneity, and existing heterogeneities. The statistical techniques differentiate between short- and long-term causality. We find that greenfield investment with a strong institution improves environmental performance, suggesting that the pollution haven hypothesis in Asian regions can be moderated by good regulation when good institutional factors are in place. Thus, greenfield investments in the presence of supporting institutions can be a viable source of green finance. In addition, our results also support the Environmental Kuznets Curve hypothesis for these economies as economic growth positively and significantly impacts environmental performance. The environmental performance of the Asian region is negatively impacted by human capital development.
Keywords: F65; Q56; O16; 330; investments; environment; economic growth; institutions